Constitutional transition to democracy in Spain - N. N. Zhukov (Ибероамериканские тетради, 2021)
In this article the author analyses formation of the country's constitutional legislation system. In the 20th century Spain experienced three different periods: the years of the Second Republic in 1931-1939, the Franco's dictatorship of 1939-1975 and the period of transition to democracy or, as it is called ‘constitutional transit' of 1975-1980, when the basic laws and regulations of democratic Spain were adopted. Each of these periods corresponded with fundamentally different lawmaking processes, based on different legal judicial norms that were strongly influenced by the peculiarities of the political situation in the country. This article examines the background of the creation of Spanish constitutions in a particular historical period, the domestic and international situation and its influence on the peculiarities of lawmaking process. The author studies the history of the constitutional documents' adoption, considers and examines their structure and content in a highly detailed way. The author scrutinizes not only the logic, but also the sequence and reasons for the adoption of all Spanish constitutional and legal acts, as well as their meaning and influence on the legal system of the state. The Fundamental Laws of Frankish Spain, as well as the Spanish Constitution of 1978, the Political Reform Act, the rulings of the Spanish Constitutional Court and other acts, the peculiarities of the transition process to democracy and the legal break with the Frankish epoch and its system of lawmaking are studied in the article. It is worth noting that, at a time when the exist opinions that the Spanish Constitution is outdated and needs reforming, the conclusion about its fundamental role for the peaceful transition to a new Spain at the end of the 20th century and its legal relevance is the issue of utmost importance.